2002
DOI: 10.1161/01.cir.0000042707.50032.19
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Reduces Atherosclerosis in Apolipoprotein E-Deficient Mice

Abstract: Background-Dysregulation of adipocyte-derived bioactive molecules plays an important role in the development of atherosclerosis. We previously reported that adiponectin, an adipocyte-specific plasma protein, accumulated in the injured artery from the plasma and suppressed endothelial inflammatory response and vascular smooth muscle cell proliferation, as well as macrophage-to-foam cell transformation in vitro. The current study investigated whether the increased plasma adiponectin could actually reduce atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
630
2
22

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 971 publications
(674 citation statements)
references
References 24 publications
20
630
2
22
Order By: Relevance
“…It reduces TNF-α-mediated adhesion of THP-1 monocytes to and induction of ICAM-1 in human coronary artery endothelial cells (HCAEC) [49]. In Apoe −/− mice, treatment with a recombinant adenovirus expressing human adiponectin resulted in increased adiponectin serum levels and decrease of atherosclerotic lesion size by about 30 % [50]. mRNA for VCAM-1 and scavenger receptor class A were significantly reduced in lesions from these mice [50].…”
Section: Adiponectin and Other Adipokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…It reduces TNF-α-mediated adhesion of THP-1 monocytes to and induction of ICAM-1 in human coronary artery endothelial cells (HCAEC) [49]. In Apoe −/− mice, treatment with a recombinant adenovirus expressing human adiponectin resulted in increased adiponectin serum levels and decrease of atherosclerotic lesion size by about 30 % [50]. mRNA for VCAM-1 and scavenger receptor class A were significantly reduced in lesions from these mice [50].…”
Section: Adiponectin and Other Adipokinesmentioning
confidence: 99%
“…In Apoe −/− mice, treatment with a recombinant adenovirus expressing human adiponectin resulted in increased adiponectin serum levels and decrease of atherosclerotic lesion size by about 30 % [50]. mRNA for VCAM-1 and scavenger receptor class A were significantly reduced in lesions from these mice [50]. Interestingly, PPARγ agonists are known to promote adipocyte differentiation and also to increase adiponectin transcription and serum levels [51].…”
Section: Adiponectin and Other Adipokinesmentioning
confidence: 99%
“…Several studies have reported the reduction of plasma adiponectin in patients with macrovascular disease 19,20 . It has also been reported that overexpression of plasma adiponectin in apo‐E KO mice improves atherosclerosis 21 . Resistin also has been reported to be involved in the development of atherosclerosis 22 .…”
Section: Discussionmentioning
confidence: 97%
“…2 Systemic clinical hypoadiponectinemia is closely associated with obesity, type 2 diabetes, and coronary artery disease (CAD). 4 Furuhashi et al recently reported that transcardiac adiponectin levels are significantly decreased in nondiabetic patients with CAD, but not in diabetic patients with the same condition.…”
Section: Introductionmentioning
confidence: 99%